2012
DOI: 10.1158/1055-9965.epi-12-0833
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Arsenic Exposure and Global Posttranslational Histone Modifications among Adults in Bangladesh

Abstract: Background Exposure to arsenic (As) is associated with an increased risk of several cancers, as well as, cardiovascular disease, and childhood neuro-developmental deficits. Arsenic compounds are weakly mutagenic, alter gene expression and post-translational histone modifications (PTHMs) in vitro. Methods Water and urinary As concentrations, as well as, global levels of histone 3 lysine 9 di-methylation and acetylation (H3K9me2 and H3K9ac), histone 3 lysine 27 trimethylation and acetylation (H3K27me3 and H3K2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
85
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 54 publications
14
85
5
Order By: Relevance
“…Furthermore, Chervona et al observed a variety of correlations between iAs exposure and this type of modification in peripheral blood mononuclear cells using a population-based study in Bangladesh. This study further revealed a positive correlation between urinary iAs and H3K9me2 (47,59).…”
Section: Histone Modificationssupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, Chervona et al observed a variety of correlations between iAs exposure and this type of modification in peripheral blood mononuclear cells using a population-based study in Bangladesh. This study further revealed a positive correlation between urinary iAs and H3K9me2 (47,59).…”
Section: Histone Modificationssupporting
confidence: 69%
“…Interestingly, these studies also showed that the iAs-induced changes in histone PTMs can be gender-specific. For instance, a decrease in H3K27ac and H3K18ac and increase in H3K4me3 and H3K27me3 was observed in iAs-exposed females, while the inverse trend was observed in iAs-exposed males (47).…”
Section: Histone Modificationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Arsenic is a well established human carcinogen, and even today millions of people are exposed to dangerous levels of naturally occurring arsenic in drinking water throughout the world (1). Exposure to a carcinogenic metal, such as arsenic, has been associated with altered gene expression patterns both in vitro and in vivo, and it has been demonstrated that the arsenicinduced changes in gene expression may be epigenetically regulated (2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The miRNAs altered in response to As exposure were also involved in one-carbon metabolism (methylation) reactions. An epidemiologic study conducted in Bangladesh, reported signifi cant associations between As exposure and global post-translational histone modifi cation in peripheral blood mononuclear cell (PBMC) DNA from a subset of participants (N = 40) enrolled in a clinical trial of folate supplementation (Chervona et al 2012 ). Arsenic levels in drinking water were positively associated with several post-translational histone modifi cations that were uniquely observed in either exposed males or females.…”
Section: Arsenic (As)mentioning
confidence: 99%